STRATEGI KOMUNIKASI PEMASARAN (Studi Pada Event Tupperware Home Party Dalam Menjaga Loyalitas Konsumen PT. Riau Cahaya Utami di Kota Pekanbaru) - Wahyu Rizky Aditya; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Sale PT. Riau Cahaya Utami increasing annualys the increase in sales is closely linked to customer satisfaction with the product tupperware so high. Costumer satisfaction is a very important thing to do with the developmentof enterprise costumer satifaction effect on loyality. In this case the tupperware home party event use the strategy to mainntain costumer loyality. Amidthe intence competition of plastic house hold products. This study aims to determine segmentation, targeting and positiong (STP) PT. Riau Cahaya Utami in the event tupperware home party and communication strategy PT. Riau Cahaya Utami through tupperware home party event in maintainning costumer loyality.This study uses descriptive qualitative data collection techniques of observation, interview anda documentation. The data obtained are then processed to be reduced, resviting conclusions presented to the public. The informan in this research consisted ofs based on purposive method that researchers use as for keabsahan examination of the data, researchers used a technique extension of participation and triangulation.The results showed the segmentation, targeting and positioning (STP) PT. Riau Cahaya Utami in the event tupperware home party segmentation.Keyword :Marketing Communication, strategy, segmentasi, targeting, positiong